Auditoría de gestión administrativa en la Cooperativa de Ahorro y Crédito “Aerocoop ltda”. del cantón Latacunga de la provincia de Cotopaxi, al período 01 de enero al 30 de junio del 2012 - Perugachi Villarruel, Verónica Lucía (2015)
The research goal is Application of an Administrative Management Audit at Cooperativa de Ahorro y Crédito “Aerocoop Ltda”. This is applied in order to analyze and develop a report that covers, recommendations and conclusions based on a technical and professional opinion. It helps to improve the company’s procedures. The methodology used to perform this research analysis was the following: observation, interview, survey, and the audit; through them we could see both as positive and negative significant results as well as they take part of this financial firm….